ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN MASALAH MATEMATIKA KONTEKSTUAL PADA MATERI SEGIEMPAT BERDASARKAN ANALISIS NEWMAN DITINJAU DARI PERBEDAAN GENDER (Studi Kasus pada Siswa Kelas VII SMPN 20 Surakarta) - Siswandi, Erlan; Sujadi, Imam; Riyadi, Riyadi (Program Studi Magister Pendidikan Matematika Fakultas Keguruan dan Ilmu Pendidikan UNS, 2016)
Abstract: The aim of this research was to identify the types of students error at 7th grade of SMPN 20 Surakarta in solving contextual mathematical problems on quadrilateral topic by using Newmanâs error analysis viewed from gender differences. The type of this research is a qualitative research. Subjectâs selection procedure was by using purposive sampling. There are 6 subjects in this research. Data collection technique was task-based interviews. The validity was determined by time triangulation. The data analysis was Miles and Huberman model including reduction, data displays, and conclusion. The results of this research showed as follows. The types of male students error in solving contextual mathematical problems based on Newmanâs error analysis were: (1) The male subject with high initial made the mistakes including transformation error and encoding error. (2) The male subject with normal initial made the mistakes including transformation error and encoding error. (3) The male subject with low initial made the mistakes including transformation error, process skills error, and encoding error. The types of female students error in solving contextual mathematical problems based on Newmanâs error analysis were: (1) The female subject with high initial made the mistakes including transformation error and encoding error. (2) The female subject with normal initial made the mistakes including transformation error and encoding error. (3) The female subject with low initial made the mistakes including comprehension error, transformation error, process skills error, and encoding error.Keywords: Contextual Problem Solving, Analysis Newman, and GenderÂ